Macrosomia Rates in Women with Diet-Controlled Gestational Diabetes: A Retrospective Study. (27th August 2017) - Vally, Fatima; Presneill, Jeffrey; Cade, Thomas
Abstract : Background . Current data on the rates of macrosomia in women with gestational diabetes mellitus (GDM) are heterogenous. No study has specifically examined macrosomia rates in women with diet-controlled gestational diabetes. Aims . To compare the rates of macrosomia between mothers with diet-controlled GDM to mothers without diabetes mellitus. Methods . A retrospective study in which all patients with diet-controlled GDM and singleton pregnancies in 2014 were considered for inclusion in the study. These cases were individually matched to mothers without GDM and without type 1 or 2 diabetes. Cases were matched to parity, age, and BMI. Controls were selected from the same year and as close as possible to the date of delivery of the case. Primary outcomes were macrosomia, defined by estimated fetal weight >90th centile and >95th centile (separately). Results . The estimated adjusted odds ratio for the presence of maternal GDM in the presence of EFW > 90th percentile (adjusted for maternal age, BMI, gravidity, parity, baby gender, and EGA) was 0.63 (95% CI 0.30–1.3; P = 0.21 ). The estimated adjusted odds ratio for the association of maternal GDM and EFW > 95th percentile was 0.66 (95% CI 0.26–1.7; P = 0.38 ). Conclusions . Our findings suggest that macrosomia is not increased in women with diet-controlled GDM. The study registration number is AQA 16/01 .